Optical coherence tomography angiography: microvascular alterations in diabetic eyes without diabetic retinopathy - Agra,Cristiana Lumack do Monte (2021)
ABSTRACT Purpose: To describe microvascular changes in the maculas of individuals with type 2 diabetes observed on optical coherence tomography angiography (OCTA) images. We compared the maculas of diabetic subjects without diabetic retinopathy with those of healthy subjects and correlated the findings with the clinical profiles of diabetic subjects. Methods: One eye each of 30 patients with diabetes and 30 healthy individuals were examined. The patients with diabetes underwent funduscopy, retinography, and fluorescein angiography to rule out retinopathy. All subjects underwent optical coherence tomography angiography of a macular area (6×6 mm2), and the foveal and parafoveal vascular densities were analyzed in the superficial and deep retinal vascular plexus. The foveal and parafoveal thicknesses, foveal avascular zone of the superficial plexus, and choriocapillaris flow area were also examined. The optical coherence tomography angiography results were compared between the two study groups and correlated with the following parameters: visual acuity, time since diabetes diagnosis, glycemic control, lipid profile, and renal function of patients with diabetes. Results: A minimal increase in the choriocapillaris flow area was observed in the patients with diabetes (mean area, 22.3 ± 4.6 mm2 in controls; 22.6 ± 3.9 mm2 in patients with diabetes) (p=0.017). No significant differences were observed between other optical coherence tomography angiography parameters analyzed in the two groups. Glycosylated hemoglobin and fasting blood glucose levels were significantly negatively correlated with the foveal vascular density of both plexuses; conversely, fasting blood glucose levels were positively correlated with the choriocapillaris flow area (p=0.034). The other clinical parameters were not correlated with the optical coherence tomography angiography findings. Conclusion: Optical coherence tomography angiography may not be the most appropriate tool for detecting preclinical changes in patients with diabetes, moreover, optical coherence tomography angiography; does not replace clinical examinations. Glycemic control should be the primary clinical parameter considered during retinopathy screening. Larger studies are necessary to confirm these findings.